Employment Law: The Richardson Years - Anderson, Gordon (Victoria University of Wellington Law Review, 2002)
This article outlines Sir Ivor Richardson’s tenure in the Court of Appeal. The author outlines the development of employment law from the early 1970s and several judgments that Richardson presided over. The author also discusses the juridification of employment law due to the enactment of key legislation and how academics responded to such a change. The author concludes that Sir Ivor Richardson’s tenure coincided with one of the most controversial and divisive periods of industrial relations in New Zealand history, meaning that the Court of Appeal had to take a leading role in determining many legal conflicts that arose as a result.